Removal of disinfection byproduct (DBP) precursors in water by two-stage biofiltration treatment. (15th October 2017) - Fu, Jie; Lee, Wan-Ning; Coleman, Clark; Nowack, Kirk; Carter, Jason; Huang, Ching-Hua
Abstract: The removal of precursors of 36 disinfection byproducts (DBPs) in effluents from flocculation/sedimentation process was evaluated across a pilot-scale two-stage biofiltration process, i.e., a sand/anthracite (SA) biofilter (empty bed contact time (EBCT) of 7.5 min) coupled with a biologically-active granular activated carbon (GAC) contactor (EBCT of 15 min). The biofiltration process exhibited a good capacity for removal of the total DBP formation potential (DBPFP) (by 25.90 ± 2.63%), and GAC contactors contributed most to the DBPFP removal (accounting for 60.63 ± 16.64% of the total removal). The removal percentage of DBPFPs of different structure types was in the following order: halonitroalkanes (58.50%) > haloaldehydes (33.62%) > haloacetic acids (HAAs, 28.13%) > haloalkanes (20.46%) > haloketones (13.46%) > nitrosamines (10.23%) > halonitriles (−8.82%) > haloalkenes (−9.84%). The precursors of bromo-DBPs (containing only bromine atoms) and maximal halogenated DBPs (containing 3 & 4 halo atoms) were removed largely compared to other DBPs. Among the total DBPFP, trihalomethanes (THMs), HAAs, and chloral hydrate were the dominant DBPs, and they accounted for >92% of the total targeted DBPs by weight. Pearson correlation analysis (CA) and principal components analysis (PCA) indicated a significant association among these dominant DBPs. Canonical correspondence analysis (CCA) revealed specific ultraviolet absorbance (SUVA254 ) could serve as a good surrogate parameter for DBPFP. Pre-chlorination upstream of the biofilters may not greatly impact the overall removal of DBPFP by SA/GAC biofiltration. In addition, results showed that SA/GAC biofiltration was a useful procedure to remove the inorganic DBP chlorite. Graphical abstract: Image 1 Highlights: The removal of 36 targeted DBP precursors by SA/GAC biofilters was evaluated. GAC contactors after SA biofilters removed the large fraction of DBPFP. The removal of individual DBPFPs showed variable results. THMs, HAAs, and chloral hydrate were the dominant DBPs in all water samples. SUVA254 may be used as a surrogate parameter for DBPFP.